1996
DOI: 10.1165/ajrcmb.15.1.8679228
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid effects in an endotoxin-induced rat pulmonary inflammation model: differential effects on neutrophil influx, integrin expression, and inflammatory mediators.

Abstract: To understand the basis for the refractory nature of acute respiratory distress syndrome (ARDS) to glucocorticoids, the effects of dexamethasone pretreatment (DEX, 2 mg/kg, intraperitoneally) on the kinetics of airway tumor necrosis factor-alpha (TNF alpha) and macrophage inflammatory protein 2 (MIP-2) production, and polymorphonuclear leukocyte (PMN) influx after intratracheal lipopolysaccharide (LPS) (1 mg/kg) in rats were investigated. In the absence of exogenous glucocorticoids, TNF alpha and MIP-2 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 36 publications
11
40
1
1
Order By: Relevance
“…Exposure to aerosolized or endotracheally administered rTNF-␣ has been associated with chemokine release in bronchoalveolar lining fluid (59), up-regulation of ICAM-1 on pulmonary vascular endothelium (23), margination of leukocytes in the pulmonary vasculature (60), and neutrophilic infiltration of the interstitium or alveolar septae (60). In agreement with published data, we found that LPS challenge induces TNF-␣ protein and/or mRNA expression in lung tissue and BAL fluid, suggesting an important role of this pleiotropic cytokine in this model (12,44,61). Furthermore, ebselen and dexamethasone were able to inhibit protein and mRNA expression for TNF-␣.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Exposure to aerosolized or endotracheally administered rTNF-␣ has been associated with chemokine release in bronchoalveolar lining fluid (59), up-regulation of ICAM-1 on pulmonary vascular endothelium (23), margination of leukocytes in the pulmonary vasculature (60), and neutrophilic infiltration of the interstitium or alveolar septae (60). In agreement with published data, we found that LPS challenge induces TNF-␣ protein and/or mRNA expression in lung tissue and BAL fluid, suggesting an important role of this pleiotropic cytokine in this model (12,44,61). Furthermore, ebselen and dexamethasone were able to inhibit protein and mRNA expression for TNF-␣.…”
Section: Discussionsupporting
confidence: 89%
“…In rats, modest glucocorticoid effects on LPS-induced lung expression of CINC and MIP-2 have been reported (42,43). The observed effect of dexamethasone on CXC chemokine BAL fluid protein level expression is largely in agreement with published data in which airway CINC-1 and/or MIP-2 expression were unaffected by glucocorticoids (36,44,45). Stimulusspecific differences in glucocorticoid sensitivity may account for the more potent effect of dexamethasone on lung CINC and MIP-2 expression observed in ozone-exposed brown Norway rats (31, 32).…”
Section: Discussionsupporting
confidence: 85%
“…In rats, modest glucocorticoid effects on LPS-induced lung expression of KC and MIP-2 have been reported in some studies [52,53]. However, our results for MIP-2 are consistent with recent reports by O'Leary et al, who found no effect of dexamethasone on MIP-2 protein levels in the rat lung in an intratracheal LPS administration model [49,54]. The possible role of endogenous glucocorticoids was not evaluated by O'Leary et al If we assume that MIP-2 is regulated similarly in rats and mice, our results extend those of O'Leary et al by showing that the lack of effect of dexamethasone on MIP-2 lung expression is not due to masking by the effects of the endogenous glucocorticoid response (as is the case for LIX).…”
Section: Differences In the Expression Of LIX Kc And Mip-2 In Endotsupporting
confidence: 93%
“…Stress can affect inflammatory diseases (see Black, 2002(Black, 2002a for review), in part mediated by the effect of stress hormones on leukocyte function (Bierhaus et al, 2006;Bilbo et al, 2002;Dhabhar, 2002;Landmann et al, 1984;O'Leary et al, 1996;Shephard, 2003), and catecholamines mediate interactions between the sympathetic and the immune systems, to alter immune cell activity (Benschop et al, 1997;Downing and Miyan, 2000;Elenkov et al, 2000;Oberbeck, 2006;Straub et al, 1998). Norepinephrine, released from sympathetic nerve terminals, and epinephrine, released from the adrenal medulla (Elenkov et al, 2000), act primarily on α 2 and β 2 adrenergic receptors expressed on most resting and activated immune cells (Barnes, 1995;Barnes, 1999;Kin and Sanders, 2006;Maestroni, 2006;Wahle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%